Asymmetrical endothelial cell migration from in vitro Quarter‐Descemet membrane endothelial keratoplasty grafts. Issue 8 (31st August 2018) - Miron, Alina; Spinozzi, Daniele; Bruinsma, Marieke; Lie, Jessica T.; Birbal, Rénuka S.; Baydoun, Lamis; Oellerich, Silke; Melles, Gerrit R.J.
Abstract: Purpose: To investigate in vitro central and peripheral corneal endothelial cell (EC) migration from Quarter–Descemet membrane endothelial keratoplasty (Quarter‐DMEK) grafts. Methods: Quarter‐DMEK grafts were obtained from 10 corneas ineligible for transplantation but with intact and viable ECs. Ten Quarter‐DMEK grafts were 'sandwiched' between two glass slides and cultured over 1 week in a humidified atmosphere at 37 °C and 5% CO2 . Cell migration was evaluated by light microscopy at standardized time intervals. In addition, immunohistochemistry analyses were performed to assess the detailed structural organization of ECs in the corneal centre and far periphery. Results: Endothelial cell (EC) migration occurred from the radial cut graft edges, but not from the far peripheral area. Cell migration followed three different migration patterns: (1) individual cell migration, (2) uncoordinated cell migration of cell clusters and (3) collective migration in which ECs moved as a sheet. Immunostaining showed the presence of ECs up to the far periphery but with different expression patterns of phenotypical markers ZO‐1, Na + /K + ‐ATPase and vimentin compared to central ECs. Conclusion: In vitro EC migration from Quarter‐DMEK grafts occurs along the radial cut edges with a decrease in migration activity towards the corneal far periphery. No migration occurred along the outer peripheral corneal edge possibly due to a different anatomical matrix in the far periphery. Hence, ECs from the far periphery may not contribute to corneal clearance of the adjacent bare area after Quarter‐DMEK surgery, but these cells may constitute a valuable cellular reserve on the graft.